Effect of Learning Think-Pair-Share Think through the combined pattern Empowerment Question on Metacognitive Skills, Creative Thinking, Understanding Concepts IPA and retention as well as Social Attitudes Students - Maryanti Ekoningtyas (Jurnal Pendidikan Sains, 2013)
Pengaruh Pembelajaran Think-Pair-Share dipadu Pola Pemberdayaan Berpikir melalui Pertanyaan terhadap Keterampilan Metakognitif, Berpikir Kreatif, Pemahaman Konsep IPA dan Retensinya serta Sikap Sosial Siswa Abstract: cooperative learning is a teaching strategy to raise awareness of student thinking, solve problems together by integrating and applying skills and knowledge, empowering metacognitive learning development, a means to teach social skills students need to live and work together. This study aims to determine the effect pattern combined PBMP TPS learning strategy against metacognitive skills, creative thinking skills, understanding of concepts, understanding of the concept of retention, and social attitudes of students. This study used a quasi-experimental approach (quasi experimental) to design non-equivalent pretest-posttest control group design. Analysis of data normality test and homogeneity test, and analysis of covariance (ANCOVA). The study population is class VIII SMPN 1 Pasuruan learning year 2012/2013. Samples were selected at random to determine the experimental class and control class. Results of the study are: (1) no influence on the strategy of metacognitive skills, creative thinking skills, understanding of concepts, and social attitudes among the students who were given a learning strategy with the given TPS PBMP multistrategi learning, (2) there is an influence on the retention of understanding of the concept among students TPS given PBMP learning strategy with a given learning multistrategi. The increase occurred in the class and the class multistrategi PBMP TPS. Key Words: TPS, PBMP, metacognitive skills, creative thinking, understanding of concepts, understanding of the concept of retention, social attitudes Abstrak: Strategi pembelajaran kooperatif merupakan pembelajaran untuk menumbuhkan kesadaran berpikir siswa, menyelesaikan masalah secara bersama dengan mengintegrasikan serta mengaplikasikan kemampuan dan pengetahuan, memberdayakan perkembangan pembelajaran metakognitif, sarana mengajarkan berbagai keterampilan sosial yang dibutuhkan siswa untuk hidup dan bekerja sama. Penelitian ini bertujuan mengetahui pengaruh pola PBMP yang dipadu strategi pembelajaran TPS terhadap keterampilan metakognitif,  keterampilan berpikir kreatif, pemahaman konsep, retensi pemahaman konsep, dan sikap sosial siswa. Penelitian ini menggunakan pendekatan eksperimen semu (quasi experiment) dengan rancangan pretest-posttest non equivalent control group design. Analisis data dengan uji normalitas dan uji homogenitas, dan analisis kovarian (ancova). Populasi penelitian ada-lah siswa kelas VIII SMPN 1 Pasuruan tahun pembelajaran 2012/2013. Sampel penelitian dipilih secara acak untuk menentukan kelas eksperimen dan kelas kontrol. Hasil penelitian adalah: (1) tidak ada pengaruh strategi terhadap keterampilan metakognitif, keterampilan berpikir kreatif, pemahaman konsep, dan sikap sosial antara siswa yang diberi strategi pembelajaran TPS+PBMP dengan yang diberi pembelajaran multistrategi, (2) terdapat pengaruh terhadap retensi pemahaman konsep antara siswa yang diberi strategi pembelajaran TPS+PBMP dengan yang diberi pembelajaran multistrategi. Peningkatan terjadi di kelas TPS+PBMP dan kelas multistrategi.    Kata kunci: TPS, PBMP, keterampilan metakognitif, berpikir kreatif, pemahaman konsep, retensi pemahaman konsep, sikap sosial